A novel nonsense mutation, E150X, in the SOX9 gene underlying campomelic dysplasia - Shotelersuk,Vorasuk (2006)
Campomelic dysplasia (CD) is an autosomal dominant skeletal malformation syndrome with features including bowed lower limbs with pretibial skin dimpling, hypoplastic scapulae and pelvic bones, and 11 pairs of ribs. Mutations in the SOX9 gene have been identified to cause CD. The gene encodes a transcription factor containing a dimerization, a high mobility group, and a C-terminal transactivation (TA) domain. Up to now, 35 SOX9 mutations have been published. In the present study, we describe a Thai girl with clinically and radiologically typical CD. Direct sequencing analysis of the PCR products for the entire coding region of SOX9 revealed that she was heterozygous for a novel 448G > T in exon 2 of SOX9. The DNA change was expected to result in E150X and loss of the entire TA domain. This result further supports that SOX9 is the only gene, discovered to date, responsible for CD across different populations and that the TA domain is important to the function of the normal SOX9.